Randomized Controlled Study of an Absorbable Vena Cava Filter in a Porcine Model - Eggers, Mitchell (J Vasc Interv Radiol, 2019)
PURPOSE: To compare the safety and efficacy of an absorbable inferior vena cava (IVC) filter and a benchmark IVC filter in a porcine model. MATERIALS AND METHODS: A randomized controlled Good Laboratory Practice study was performed in Domestic Yorkshire cross swine. Sixteen swine were implanted with an absorbable IVC filter (test device; Adient Medical, Pearland, Texas); 8 were implanted with a benchmark metal IVC filter (control device; Cook Medical, Bloomington, Indiana). All animals underwent rotational digital subtraction pulmonary angiography and cavography (anteroposterior and lateral) before filter deployment and 5 and 32 weeks after deployment. Terminal procedures and necropsy were performed at 32 weeks. The IVC, heart, lungs, liver, and kidneys were harvested at necropsy. The reported randomized controlled GLP animal study was conducted at Synchrony Labs, Durham, North Carolina. RESULTS: One animal died early in the test cohort of a recurring hemorrhage at the femoral access site resulting from a filter placement complication. All other animals remained clinically healthy throughout the study. No pulmonary embolism was detected at the 5- and 32-week follow-up visits. The absorbable filter subjects experienced less caval wall perforation (0% vs 100%) and thrombosis (0% vs 75%). The control device routinely perforated the IVC and occasionally produced collateral trauma to adjacent tissues (psoas muscle and aorta). The veins implanted with the absorbable filter were macroscopically indistinguishable from normal adjacent veins at 32 weeks except for the presence of radiopaque markers. Nontarget tissues showed no device-related changes. CONCLUSIONS: Implantation of the absorbable IVC filter in swine proved safe with no pulmonary emboli detected. There was complete to near-complete resorption of the filter polymer by 32 weeks with restoration of the normal appearance and structure of the IVC.